1995
DOI: 10.1148/radiology.197.2.7480700
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception: ability of fluoroscopic images obtained during air enemas to depict lead points and other abnormalities.

Abstract: Successful reduction of an intussusception does not always rule out a lead point. Other imaging studies, the patient's condition, and laparotomy may also be necessary to diagnose and treat lead points and other lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 0 publications
2
39
2
2
Order By: Relevance
“…Although an LP was determined as the cause of intussusception in only 3% of the cases where intussusception was seen below the age of 1 year, this rate may increase to 57% in children aged over 3 years. [2,9,10] In the current study, during surgery was observed LP in 13.9% of cases.…”
Section: Discussionsupporting
confidence: 51%
“…Although an LP was determined as the cause of intussusception in only 3% of the cases where intussusception was seen below the age of 1 year, this rate may increase to 57% in children aged over 3 years. [2,9,10] In the current study, during surgery was observed LP in 13.9% of cases.…”
Section: Discussionsupporting
confidence: 51%
“…There are many types of contrast agents [5,[8][9][10][11][12]; the efficiency of air enema method in our series was 87%, and the complications are extremely rare and are usually avoidable.…”
Section: Discussionmentioning
confidence: 55%
“…Early hospitalization and appropriate (conservative or surgical) treatment usually provide favourable outcomes. Conservative reduction is globally employed and, as a rule, is effective; but in different countries different agents are injected: liquid [8], air [9,10], barium [11,12]. In China, the successful rate of the reduction is about 95% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pathological lead points in children may also include Meckel diverticulum, duplication cysts, lymphoma, hemangioma and appendix [7][8][9]. Fluoroscopic images during reduction tend to miss pathological lead points [13], however with wide use of ultrasound as a main diagnostic tool in cases of suspected intussusception, pathological lead points may often be demonstrated at the time of diagnosis. US has been reported as having 100% negative predictive value for intussusception diagnosis [6], and also allows preoperative identification of 66% of the lead points and specific diagnosis in 48% [7].…”
Section: Discussionmentioning
confidence: 99%